Empyema thoracis in children: analysis from a tertiary care center - Thakkar, Parth K.; Shendurnikar, Niranjan; Desai, Hitesh; Doshi, Vikas (International Journal of Contemporary Pediatrics, 2021)
Background: Empyema thoracis refers to infection and pus formation within the pleural space in the thorax. It is estimated that 0.6% of childhood pneumonia’s progress to empyema, affecting 3.3 per 100000 children. The purpose of this study was to analyse the clinical and bacteriological profile, outcome of empyema in children with reference to intercostal drainage/tube thoracostomy (ICD/TT) and video assisted thoracoscopic surgery (VATS). Methods: A hospital based prospective comparative study was conducted on 61 children diagnosed with empyema thoracis according to ICD-10 code J869 between 6 months to 18 years of age admitted to K. G. P. children hospital, Vadodara over a period of 20 months from September 2018 to May 2020. Results: Most of patients (63.9%) were seen in age group of 1-5 years. Fever (100%), cough (99%) and breathlessness (85%) were the commonest presenting features. Pleural fluid culture was positive in (28%) of patients and Staphylococcus aureus (11.5%) was the most frequent organism isolated from pleural fluid. The mean duration of ICU stays, the mean duration of hospital stays and time taken for removal of ICD was less VATS group with statistically significant difference. Conclusions: Empyema in children causes significant morbidity which can be reduced by appropriate treatment of bacterial pneumonia. ICD and antibiotics are effective method to facilitate drainage and resolution of empyema in resource poor settings. VATS is effective treatment for empyema when presented with stage 2 and stage 3 empyema having multiple loculation, which decreases duration of hospital treatment.